Global status and attributable risk factors of breast, cervical, ovarian, and uterine cancers from 1990 to 2021 - Tianye Li; Haoxiang Zhang; Mengyi Lian; Qionghua He; Mingwei Lv; Lingyun Zhai; Jianwei Zhou; Kongming Wu; Ming Yi (Journal of Hematology & Oncology)
Abstract Background Female-specific cancers, particularly breast, cervical, ovarian, and uterine cancers, account for nearly 40% of all cancers in women. This study aimed to analyze the global epidemiological trends of these cancers from 1990 to 2021, offering insights into their evolving patterns and providing valuable information for health policymakers to allocate healthcare resources more effectively. Methods Data from the Global Burden of Disease Study 2021 (GBD 2021) were used to comprehensively assess the global incidence, mortality, and disability-adjusted life years (DALYs) of female-specific cancers. Age-standardized rates facilitated cross-regional comparisons, accounting for differences in population size and demographics. The socio-demographic index (SDI) was employed to categorize regions and evaluate correlations between cancer burden and economic level. In addition, risk factors attributable to female-specific cancer deaths and DALYs were assessed based on the comparative risk assessment model of the GBD project. Results From 1990 to 2021, the global burden of female-specific cancers increased at varying rates. In 2021, breast cancer accounted for 2.08 million incident cases, 0.66 million deaths, and 20.25 million DALYs globally. In comparison, cervical, ovarian, and uterine cancers had lower burdens, with 0.67 million, 0.30 million, and 0.47 million incident cases, respectively. Age-standardized rates of breast, ovarian, and uterine cancers showed positive correlations with SDI, while cervical cancer exhibited a negative correlation. Attributable risk factors for breast cancer-associated deaths in 2021 included dietary risks, high body-mass index (BMI), high fasting plasma glucose, alcohol use, tobacco use, and low physical activity. Additional risk factors were unsafe sex and tobacco use for cervical cancer, high BMI and occupational risks for ovarian cancer, and high BMI for uterine cancer. Conclusions The burden of female-specific cancers has increased in recent decades, with significant demographic and regional discrepancies. These findings highlight the urgent need for targeted public health interventions to mitigate the global impact of these cancers.